Direito das crianças à educação em creches na cidade de Manaus - Ribeiro, Fabrícia Tavares (2019)
This study was developed from the research line, Intangible Capital: production and circulation of knowledge, and whose interest is the right of children to education, a right that is inserted as one of the main fundamental rights in the Federal Constitution of 1988, fabric together with historical contextualization. Its general objective is to analyze the civil responsibility in the face of the omission of the municipality of Manaus in the provision of the public service of creches. The research is documentary type. The work will reflect reflexively on the historical context of the right to education of children in international scope, in Brazil and, finally, in Manaus. The struggle of social movements for overcoming the assistance aspect and prevalence of the educational perspective in public day care centers was a relevant achievement, as well as the inclusion of these spaces in the educational system. We will also discuss educational legislation and its applicability. The CF / 88 gave the child the value of the Subject of Rights par excellence, therefore carrying innumerable rights, including access to quality education at any stage, including public day care centers. As to the foundation of this right, the Magna Carta established the division of legislative and administrative competencies between the federated entities, as well as the priority competence of the Municipality; in terms of achievement, the allocation of public resources and the co-responsibility of the State, the family and society are foreseen, since there is no way of talking about education without the participation of these three actors in the process. The relevance of Early Childhood Education is enshrined throughout the Constitution and LDB. The existence of the National Education Plan and the Municipal Plan of Education, as State policies contributes to the improvement of the attendance at this stage of education. However, the non-provision of day-care education is treated as civil liability of the municipality of Manaus, and if confirmed, we will have its omission mainly due to violation of a constitutional order.